Evaluasi Perencanaan Infus Di Instalasi Farmasi Rumah Sakit ‘X’ Mojokerto Periode Januari – Desember Tahun 2022 - nur aini; Novia Ariani (Jurnal Farmasi Indonesia AFAMEDIS, 2023)
Abstract Drug planning is an activity process in selecting the type, quantity and price of pharmaceutical supplies according to the needs and budget. An effective planning process is to ensure the availability of drugs so as to avoid drug shortages and excesses. This study aims to determine and evaluate infusion planning at Hospital 'x'. There are 23 items of infusion type at Hospital 'x' in 2020. This research is a non-experimental study using a retrospective method. This research was conducted at the Hospital 'x' Mojokerto. Methods of data collection This study used primary data derived from interviews with the head of the pharmacy installation, as well as secondary data derived from drug planning data and infusion stock-taking reports at Hospital 'x'. Furthermore, the research results are compared with standard indicators. The results showed that the planning indicator was the percentage of the number of drug items that were held as planned (57%), the planning indicator was the percentage of the budget (97%). The planning for the realization budget has been efficient but is still not fullyeffective and needs to be improved, especially the drug planning process